Cournot conjectures under price competition. (22nd May 2018) - Delbono, Flavio; Lambertini, Luca
Abstract: In a homogeneous oligopoly, under standard regularity conditions, we prove that the Cournot–Nash equilibrium emerges under price competition and Cournot conjectures. We illustrate this result also under exogenous product differentiation.